Implementation of zakat and waqf in Comoros: an empirical assessment - Bacha, Asmaou Mohamed; Zakariyah, Habeebullah (MIH Training and Consultancy Services and Al Hikmah Research, 2025)
Zakat and waqf represent key instruments of Islamic social finance with the potential to advance socio-economic development in Muslim societies. In Comoros, a country where Islam shapes both culture and institutions, these instruments are formally established and widely acknowledged. The aim of this study is to assess the implementation of zakat and waqf in Comoros. A qualitative approach was used combining focus group discussions with zakat and waqf experts and a semi-structured interview with the Kadi, a recognized authority in Islamic jurisprudence. The findings reveal that although awareness of zakat and waqf is widespread, there remains a limited awareness of their developmental potential. Furthermore, institutional practices are largely confined to meeting immediate consumption needs, with few structured initiatives directed toward sustainable, long-term socio-economic growth. This study contributes to the limited literature on Islamic social finance, particularly in Comoros and it highlights practical pathways for strengthening zakat and waqf as instruments of sustainable development in the Comorian context